1999
DOI: 10.1001/archpedi.153.8.834
|View full text |Cite
|
Sign up to set email alerts
|

Douching

Abstract: To compile available published data on the prevalence of douching practices in adolescent girls and young women and the effects of douching on gynecologic health, including studies of gynecologic changes due to douching in adolescent girls and young women, surveys that demonstrated the prevalence of douching in the populations, and policy statements or lack thereof from professional and medical organizations with regard to the practice of douching.Data Sources: We did Internet searches, including a MEDLINE sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Vaginal douching remains controversial. It has often been linked to increased risks of pelvic inflammatory disease, ectopic pregnancy, reduced fertility, and bacterial vaginosis [5][6][7]. However, recent studies in low-income countries concluded that, in certain circumstances, it may be beneficial [8][9][10][11][12], and our study results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Vaginal douching remains controversial. It has often been linked to increased risks of pelvic inflammatory disease, ectopic pregnancy, reduced fertility, and bacterial vaginosis [5][6][7]. However, recent studies in low-income countries concluded that, in certain circumstances, it may be beneficial [8][9][10][11][12], and our study results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Without a frame of reference for “normal” vaginal microbiota in healthy adolescents, the clinical relevance of microbiota resembling that associated with bacterial vaginosis is uncertain. Furthermore, as girls progress into menarche, menstrual hygiene behaviors, including use of menstrual pads and tampons, bathing habits, and douching, may alter existing vaginal microbiota ( 20 , 25 30 ). Finally, changes in the early vaginal microbiota may have lasting influences on subsequent vaginal health, but our understanding of the complex interactions of immune tolerance of indigenous bacterial populations, immune surveillance for vaginal pathogens, variability in vaginal microbiota, and reproductive health outcomes remains primitive ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have identified no significant association between vaginal douching and PID 47 , bacterial vaginosis 13, 48 , Chlamydia 2, 36, 38 , trichomonasis 13, 3637 , or gonorrhea. 2, 36, 38 The apparent discrepancy between studies may be attributable, in part, to inconsistencies between study samples in the types of products used for vaginal douching 44 , reasons for vaginal douching 49 , frequency and duration of vaginal douching 14, 19, 4243 , and timing in relation to sexual activity and menses. 49 For example, certain studies have specifically identified that the association between vaginal douching and PID 19 , bacterial vaginosis 14 and Chlamydia 4243 is dependent on frequency of douching.…”
Section: Introductionmentioning
confidence: 99%
“…2, 36, 38 The apparent discrepancy between studies may be attributable, in part, to inconsistencies between study samples in the types of products used for vaginal douching 44 , reasons for vaginal douching 49 , frequency and duration of vaginal douching 14, 19, 4243 , and timing in relation to sexual activity and menses. 49 For example, certain studies have specifically identified that the association between vaginal douching and PID 19 , bacterial vaginosis 14 and Chlamydia 4243 is dependent on frequency of douching. Outcomes may also vary as a function of type of solution used to douche; one study suggests that vaginal douching with non-commercial preparations is associated with an increased prevalence of HIV, while vaginal douching with commercial preparations is associated with decreased HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%